Case Study of Computer Network Development for the Internet Of Things (IoT) Industry in an Urban Environment - Rachman, Anang Fakchtur; Putra, Fauzan Prasetyo Eka; Syirofi, Syirofi; Wahid, Durrahman (Yayasan Cita Cendekiawan Al Khwarizmi, 2024)
This research presents a case study of computer network development to support the Internet of Things (IoT) industry in an urban environment. The rapid growth of the IoT industry has created the need for a network infrastructure that can support the connectivity of various smart devices widely and reliably. This research focuses on urban environments that have unique complexities such as high population density, intensive movement, and diverse infrastructure needs. The research methodology involves a detailed analysis of the implementation of computer networks in the context of the IoT industry in urban environments. Data was collected through field observations, interviews with experts, and analysis of relevant project documents. The analysis results show that the development of computer networks in urban environments to support industrial IoT requires scalable network design, efficient bandwidth management, tight security, and adaptation to existing infrastructure. This case study describes various strategies and technologies used in the development of computer networks, including the implementation of 5G-based wireless networks and the monitoring of urban environments using smart sensors. These results highlight the importance of a holistic and sustainable approach when developing computer networks for the IoT industry in urban environments. Ensuring your infrastructure can meet future needs requires collaboration between stakeholders, investment in the right technology, and careful planning. This study makes an important contribution to the optimisation of computer networks that support the growth of the IoT ecosystem in urban environments.